Assessment of Selection Criteria for Development of High Yielding Genoptypes Using Variability Parameters in Lemongrass Cymbopogon flexuosus L. Issue 6 (2nd November 2017) - Dutta, Sukriti; Munda, Sunita; Chikkaputtaiah, C.; Lal, Mohan
Abstract: Lemongrass ( Cymbopogon flexuosus L.) is an essential oil yielding perennial grass of Poaceae family. Owing to its several industrial and pharmaceutical applications, Lemongrass is gaining global significance off late. A field experiment was conducted at CSIR-NEIST Jorhat with 120 genotypes of Lemongrass from 2014-2017. It was observed that the genetic differences were highly significant for key agronomic traits such as plant height, tillers/plant, citral content, herbage yield (q/ha) and oil yield (q/ha). High heritability was observed for all the traits except citral content. High heritability with low genetic advance was recorded for plant height indicated that this trait is under non-additive gene action. Oil yield (q/ha) and tillers /plant were inversely proportional to the citral content of Lemongrass. Similarly, plant height was also inversely correlated with tillers/plant. However, the oil yield (q/ha) were directly proportional to herbage yield (q/ha). The result of high heritability with high genetic advance observed for herbage and oil yield would be helpful for the improvement and assessment of selection criteria in identification of superior germplasm of Lemongrass. Moreover, positive correlation of herbage yield with oil yield would be helpful in the selection of a better genotype, which will ultimately lead to an improved economic status of the country as well as the whole world. Based on the above findings, further study may be carried out for the identification of new and improved varieties with high oil yield of Lemongrass ( C. flexuosus ).